Maintaining Business Sustainability: Challenges and Opportunities of Sustainability Reporting in Indonesia - Alwyah, Lila (Business Management, 2025)
This study aims to discuss the importance of sustainability reporting for companies, the condition of sustainability reporting in Indonesia, and the challenges and opportunities faced in implementing it. The method used in this study is library research that refers to the results of previous studies. Based on the findings from previous studies, Indonesia has not yet implemented mandatory regulations for the presentation of sustainability reports. The absence of strict regulations related to sustainability reporting has resulted in only a few public companies in Indonesia committing to supporting sustainability reporting. The challenges in implementing sustainability reporting in Indonesia include a lack of awareness, a lack of government policy, and a lack of resources. The opportunities in implementing sustainability reporting in Indonesia include improving the company's image, attracting investors, and meeting consumer demands.